IMPlementing IMProved Asthma self-management as RouTine (IMP2ART) in UK primary care: An internal pilot for a cluster randomised controlled trial - Kirstie McClatchey; Daisy Bertram; Atena Barat; Brigitte Delaney; Vicky Hammersley; Barbara Korell; Viv Marsh; Megan Preston; Jessica Sheringham; Liz Steed; Steven Julious; David Price; et al. (PLoS ONE, 2026)
Introduction Supported self-management that includes a personalised asthma action plan and regular professional review, reduces unscheduled consultations, and improves asthma outcomes and quality of life. However, despite unequivocal inter/national guideline recommendations, supported self-management is poorly implemented in UK primary care. The IMPlementing IMProved Asthma self-management as RouTine (IMP 2 ART) implementation strategy (including facilitated provision of patient, professional, and organisational resources) has been developed to address this challenge and is being evaluated in a UK-wide cluster randomised controlled trial (cRCT). The internal pilot aimed to assess the trial recruitment processes, delivery of and general practice engagement with the implementation strategy to inform the progression criteria. Methods Using mixed methods, we recruited 12 general practices and monitored trial processes and IMP 2 ART delivery through team logs and automated data (e.g., use of patient online resources; uptake of practice education modules). Qualitative interviews with general practice staff and IMP 2 ART facilitators explored feasibility and acceptability of the implementation strategy. Results We randomised 12 general practices to the IMP 2 ART implementation strategy arm (n = 6) or usual asthma care (control, n = 6). One control practice withdrew post-randomisation following concerns about data sharing. Most components were delivered successfully to the implementation group practices so that we met our progression criteria. In all six practices, the facilitated workshop was arranged within 12 weeks of randomisation and the team education module was completed (median 11 accesses/practice), the in-depth module was completed by ‘the healthcare professional responsible for asthma reviews’ (range 3-7 professionals/practice), and the asthma review template was successfully downloaded to the practice system. All six implementation practices received the baseline and first monthly audit and feedback report although there were delays in this process due to national-level governance changes. Practices’ perceptions of IMP 2 ART were encouraging. In general, they participated in the patient, professional and organisational implementation strategies and reported positive experiences of the trial. Conclusions The study provides evidence that the IMP 2 ART trial is feasible, and the implementation strategy is acceptable with only minor adjustments to trial processes. The IMP 2 ART strategy is now being tested in a UK-wide cRCT [ref: ISRCTN15448074], evaluating implementation (action plan ownership) and health outcomes (unscheduled care).